Randomized, controlled clinical trial to evaluate efficacy of sticky bone and concentrated growth factor in the management of intrabony defects: 12 months follow-up study - Dhanashree Ghoderao; Surekha Rathod; Abhay Pandurang Kolte; Pranjali Bawankar; Ashwini Jadhav (Wolters Kluwer Medknow Publications, 2022)
Background: Platelet derivatives are enriched growth factors that ameliorate various cellular processes in regeneration. The present clinical trial aimed to evaluate and compare the effects of sticky bone and concentrated growth factors (CGFs) in the treatment of intrabony osseous defects by cone-beam computed tomography (CBCT). Materials and Methods: The study included 20 patients having 40 intrabony defects. 20 sites each were included in both test group (Sticky bone) and Control group (CGF alone). The clinical parameters including probing pocket depth (PPD) and clinical attachment level (CAL) were assessed at baseline and 6 and 12 months posttherapy. The radiographic parameters including the depth, mesiodistal (MD), and the buccolingual (BL) width of the defect to assess the amount of bone fill were examined at baseline and after 12 months using CBCT. Results: Twelve months posttherapy clinical results indicated a significant reduction of PPD and gain in CAL in both the study groups. Similar observations were recorded with CBCT radiographic parameters where the intrabony defect depth and MD defect width for the test group and control group significantly reduced after 12 months' posttherapy (P < 0.0001). However, no significant reduction in BL defect width was observed in control group (P = 0.577) in contrast to the test group (P = 0.028) after 12 months' posttherapy. Conclusion: Intrabony defects treated with sticky bone showed improved clinical and radiographic parameters indicative of enhanced periodontal regeneration as compared to CGF alone treated sites.